A dual source fed eleven level switched capacitor multilevel inverter with voltage boosting capability - Hussain, Md Tahmid; Tariq, Mohd; Sarwar, Adil; Ahmad, Shafiq; Poshtan, Majid; Mahmoud, Haitham A. (Frontiers in Energy Research, 2024)
Multilevel inverter has grown substantially in popularity because of superior power quality. This work presents an 11-level switched-capacitor multilevel inverter (SCMLI) with 1.67-times boosting capability for solar photo-voltaic (PV) application. Using 12 switches, 2 DC supply and 2 capacitors, an 11-level output voltage waveform is achieved. For this, only seven driver circuits are necessary since the topology makes use of 2 bidirectional switches and 3 pairs of switches that are complementary in nature. The proposed inverter has intrinsic capacitor self-balancing features since the capacitors are connected across the DC voltage source at different times throughout a basic cycle to charge the capacitors at a level of input voltage. A thorough comparison between the topology and recently developed SCMLI's has been presented. The comparison demonstrates the effectiveness in terms of switches, capacitors, sources, efficiency, total standing voltage (TSV), and boosting capacity. The performance of the suggested SCMLI is then experimentally tested by using a profound frequencybased switching method. The suggested topology generates 7.65% of THD in its output voltage waveform.